1973
DOI: 10.7164/antibiotics.26.521
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bleomycin on Sv40 Dna: Characteristics of Bleomycin Action Which Produces a Single Scission in a Superhelical Form of Sv40 Dna

Abstract: The effect of bleomycin on the molecular integrity of SV40 DNAwas determined under various conditions by taking advantage of the fact that a single scission produced in such a superhelical form of DNAcould be clearly manifested by analysis of samples with centrifugation in alkaline sucrose gradients. Conditions were found where the reaction velocity, the rate of disappearance of the characteristic form of DNA,depended on the concentration of bleomycin as well as on the reaction time. In contrast to general enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1977
1977
1991
1991

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…One test for an intercalator is its ability to relax supercoiled DNA without nicking the DNA strand (Waring, 1970). At low pH, bleomycin binds to DNA, but its nicking activity is greatly inhibited (Umezawa et al, 1973;Chien et al, 1977). When ColEl supercoils were sedimented in gradients at pH 5.5, presence of bleomycin caused a movement of the supercoil peak to coincidence with that of nicked circles (Figures 2 and 3A).…”
Section: Resultsmentioning
confidence: 97%
“…One test for an intercalator is its ability to relax supercoiled DNA without nicking the DNA strand (Waring, 1970). At low pH, bleomycin binds to DNA, but its nicking activity is greatly inhibited (Umezawa et al, 1973;Chien et al, 1977). When ColEl supercoils were sedimented in gradients at pH 5.5, presence of bleomycin caused a movement of the supercoil peak to coincidence with that of nicked circles (Figures 2 and 3A).…”
Section: Resultsmentioning
confidence: 97%
“…The dependence of the reaction of DNA with Fe(II) and bleomycin on pH differs from the pH dependence observed in the absence of reducing agents (Umezawa et al, 1973) and in the presence of Mg(II)-ATP (Takeshita et al, 1977). In both of these studies substantial activity below pH 7 was not observed, in contrast to our results.…”
Section: Discussionmentioning
confidence: 92%
“…In several studies, divalent metal ions (including cobalt) that compete with iron for the same binding sites on BLM have been found to suppress the cleavage activity of BLM on isolated DNA (Suzuki et al, 1970;Umezawa et al, 1973;Takeshita et al, 1976; Lown & Sim, 1977;Sausville et al, 1978). It is nevertheless possible that metallobleomycins other than iron bleomycin may induce cleavage of DNA under conditions that are somewhat different from those used previously.…”
mentioning
confidence: 99%